EGR1 is essential for transcriptional regulation of BMPR2 - Gaddipati, Radhika; West, James D.; Loyd, James E.; Blackwell, Thomas; Lane, Kirsten A.; Lane, Nicole M.; Lane, Kirk B. (Scientific Research Publishing, 2011)
In this study, RLM-RACE was used to identify the transcriptional start site 387 bp upstream of the translational start. Evolutionarily conserved transcription factor binding sites were identified, and a series of luciferase reporter constructs driven by BMPR2 promoter elements used to determine their functional relevance. We found the promoter area from 983 bp to 90 bp upstream of the transcriptional start gave maximal activity, greater than longer constructs, with an area between 570 bp and 290 bp upstream of the transcriptional start containing an important repressor element. To characterize this repressor, we used a combination of EMSA, mutation of the EGR1 binding site, transfection with EGR1 and NAB1 constructs, and mutation of the NAB1 binding site within the EGR1 protein. From this we conclude that EGR1 is essential to BMPR2 transcription, but that NAB1 binding to EGR1 causes it to act as a repressor.
Keywords: Transcription; BMPR2 Regulation; EGR1; NAB1; Pulmonary Hypertension